Respuesta :

Answer:

x = 8.6

Simplifying

5x + -43 = 0

Reorder the terms:

-43 + 5x = 0

Solving

-43 + 5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '43' to each side of the equation.

-43 + 43 + 5x = 0 + 43

Combine like terms: -43 + 43 = 0

0 + 5x = 0 + 43

5x = 0 + 43

Combine like terms: 0 + 43 = 43

5x = 43

Divide each side by '5'.

x = 8.6

Simplifying

x = 8.6

Step-by-step explanation:

Hope it is helpful...

x = 8.6
43 divided by 5 = 8.6
ACCESS MORE